1992
DOI: 10.1111/j.1600-065x.1992.tb00835.x
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Immunoglobulin Variable Regions in Autoimmunity to DNA

Abstract: Results from our analyses of variable region gene usage among spontaneous anti-DNA antibodies in autoimmune mice have indicated that both the early IgM and later-appearing IgG autoantibodies to DNA are generated by clonally selected B cells. The recurrent usage of particular variable region genes among all the anti-DNA hybridomas analyzed and reported to date supports this hypothesis. The preferential expression of particular light and heavy chain variable region genes among selected populations of both IgM an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
62
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 56 publications
5
62
1
Order By: Relevance
“…However, besides the changes reported in Table I, no further residue usage differences were noted in the CDR3 regions of ANA LCs. For instance, previous studies have suggested that R residues at L96 arising as a consequence of V-J1 joining were particularly prominent among anti-dsDNA Abs (8,40,41). However, in the present analysis, the frequency of R at L96 was almost identical between anti-dsDNA Abs and the non-ANA controls, arising in both cases as a consequence of rearrangement to J1.…”
Section: Discussioncontrasting
confidence: 79%
“…However, besides the changes reported in Table I, no further residue usage differences were noted in the CDR3 regions of ANA LCs. For instance, previous studies have suggested that R residues at L96 arising as a consequence of V-J1 joining were particularly prominent among anti-dsDNA Abs (8,40,41). However, in the present analysis, the frequency of R at L96 was almost identical between anti-dsDNA Abs and the non-ANA controls, arising in both cases as a consequence of rearrangement to J1.…”
Section: Discussioncontrasting
confidence: 79%
“…Numerous studies have shown that the autoantibodies produced in systemic autoimmune disease states, particular to nuclear autoantigens, bear the hallmarks of transit through the GC/memory pathway: heavily somatically mutated V regions and recurrent types of mutations that increase affinity for cognate autoantigen (e.g., resulting in the introduction of arginines in CDRs) (62,63). If Fcā„RIIB does not directly participate in the negative selection of autoreactive B cells during the GC/memory B cell pathway how, then, can the pivotal contribution of a deficiency of this receptor to the development of autoimmune disease on certain mouse and human genetic backgrounds be explained?…”
Section: Discussionmentioning
confidence: 99%
“…The nucleotide sequences contributing to DNA binding have been a subject of intense study in recent years (12,(28)(29)(30). The basic amino acids arginine (R) and lysine (K) are capable of interacting with DNA or with its deoxyribose phosphate backbone.…”
Section: Discussionmentioning
confidence: 99%